Peri operative diabetic management using subcutaneous regular insulin as sliding scale and alberti regimen of glucose insulin potassium infusion - comparative study (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background The management of diabetic patient during the peri-operative period can be a problem to the anaesthesiologist. Many of worker have used short acting regular insulin using sliding scale which starts before operation and continue in post operatively. Alberti and Thomas proposed a simple regimen using a cotinuous intravenous infusion of an glucose insulin potassium (GIK) solution which is administered during the prei-operative period. Objectives The aim of the study is to observe the rise of blood sugar in diabetic patients per and post operatively and to detrermine the more acceptable method of controlling blood sugar amongst two predetermined methods. Methods A total of 80 patients of ASA II & III were randomly selected. They were divided into the following groups. Group A. forty patients were randomly allocated to the treatment of thrice daily subcutaneous injections of short acting regular insulin by sliding scale. Group B. Forty patients were randomly allocated to continuous glucose insulin potassium treatment (GIK). Pre-operative blood glucose was controlled with thrice daily subcutaneous injection of short acting regular insulin. Result The two groups were comparable in demographic data. The blood glucose of group A was raised at mid operation, after 8 hours, 16 hours and 24 hours of operation more than the group B and it were statistically significant. Serum potassium level of the two group did not show any significant difference. The study showed that group B can produce satisfactory blood sugar and serum potassium control than group A. It is safe, simple and less expensive and can be apply in any situation. Conclusion Due to the large number of diabetic patients undergoing surgery and probable complications associated with diabetes, careful perioperave evaluations and management are required in these patients. To select an appropriate interventional strategy depends on the patient, the associated diabetic complications and type of surgery. Chronic diabetic complications can influence surgery and anesthetic conditions. Hence, appropriate risk stratification, optimal blood glucose and suitable interventional strategy are necessary. Glucose insulin potassium infusion can minimize metabolic disturbances during surgery. DOI: http://dx.doi.org/10.3329/jbsa.v26i1.19816 Journal of Bangladesh Society of Anaesthesiologists 2013; 26(1): 45-51